1970
DOI: 10.1107/s0021889870006131
|View full text |Cite
|
Sign up to set email alerts
|

Fan texture of the compound Ba3Co2Fe24O41prealigned in a magnetic field

Abstract: Samples of the ferrimagnetic material Ba3Co2Fe24041, pre-aligned in a magnetic field and sintered at various temperatures, have been examined for preferred orientation. Schulz's reflexion technique and the standardizing method of Holland were used to determine quantitative pole figures of several lattice planes. The texture bears a close resemblance to a 'fan texture' in which the crystallites have their basal planes parallel to a preferred direction. The sharpness of the texture increases with increasing sint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A corl'ection has to be made for the occurrence of defocusing of the diffracted X-ray beam caused by the geometrical configuration of the instrument. In our work on the fan texture of the pre-aligned ferromagnetic material Ba3Co2Fe2404~ (Huijser-Gerits, Rieck & Vogel, 1970), it was found that ignorance of the defocusing correction introduces a spurious maximum in the centre of most pole figures. In this case it was necessary to correct the data for defocusing even in qualitative work in order to get a description of the texture.…”
Section: Introductionmentioning
confidence: 90%
“…A corl'ection has to be made for the occurrence of defocusing of the diffracted X-ray beam caused by the geometrical configuration of the instrument. In our work on the fan texture of the pre-aligned ferromagnetic material Ba3Co2Fe2404~ (Huijser-Gerits, Rieck & Vogel, 1970), it was found that ignorance of the defocusing correction introduces a spurious maximum in the centre of most pole figures. In this case it was necessary to correct the data for defocusing even in qualitative work in order to get a description of the texture.…”
Section: Introductionmentioning
confidence: 90%
“…The textureless samples (a) are prepared and selected according to Huijser-Gerits & Rieck (1974a, b). The samples with fibre texture (b) are made as described by Huijser-Gerits & Rieck (1974b) and those with fan texture (c) according to Huijser-Gerits, Rieck & Vogel (1970). The measuring techniques used are also described in these previous papers.…”
Section: Methodsmentioning
confidence: 99%
“…The measuring techniques used are also described in these previous papers. Crystallographic textures are determined as done by Huijser-Gerits, Rieck & Vogel (1970). In order to obtain standardized intensities for a sample with a certain amount of texture, the measured intensities have to be corrected for changes in focusing conditions at different tilting angles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used to obtain the preferred orientation of the samples quantitatively by means of pole figures, standardized by making use of random samples, has been discussed earlier by Huijser-Gerits, Rieck & Vogel (1970). With this method pole figures of several reflexion planes were determined.…”
Section: Measurement Of the Crystallographic Texturementioning
confidence: 99%